Green Synthesis of Gold Nanoparticles using Peronema canescens Leaves Extract and Their Catalytic Performance for Dyes and Nitro Compounds - Falahudin, Aswin; Insin, Numpon; Yudha S, Salprima; Adfa, Morina (Molekul, 2023)
The most interesting and well-known research in the field of gold nanomaterials synthesis is the use of "green chemistry" to prepare gold nanoparticles (AuNPs). In this study, Peronema canescens leaf extract was used as the synthesis medium to successfully produce AuNPs in a way that was cheap, quick, and good for the environment. A UV-visible spectrophotometer, particle size analysis (PSA), and transmission electron microscopy (TEM) were used to find out more about the AuNPs that were prepared. The UV-visible spectrophotometer showed a surface plasmon resonance peak at 532 nm, which proves https://www.fortyouncewines.com/ that AuNPs exist in the solution. TEM and PSA both showed that the AuNPs were mostly spherical and had an average diameter of 14.9 nm, respectively. In the presence of NaBH4, the AuNPs were found to speed up the reduction of rhodamine B (RhB), metanil yellow (MY), and 4-nitrophenol (4-NP). The results show that the AuNPs that were prepared in a new way worked very well and could be used in catalysis.